Discrete Mathematice: with graph theory and combinatorices - Veerajan, T (Tata McGraw-Hill, 2007)
Discrete Mathematice: with graph theory and combinatorices / Veerajan, T. -- New Delhi: Tata McGraw-Hill, 2007 511.3 V419 No. of Copies : 1